(untitled) (Vallis Aurea, 2021)
The purpose of this paper is to investigate whether self-organisation predicts of adoption of management controls in manufacturing firms. The study employed the lens of complex adaptive systems theory to investigate the research question. The study used a cross-sectional survey to collect data from 202 manufacturing firms with the use of a multi-dimensional self-administered questionnaire Data were analyzed quantitatively using PLS-SEM. The findings indicate a positive relationship between innovativeness, emergence and adoption of management controls. The hypothesis for networks of interaction was not supported.